Development of a communication environment between IPv6 and IPv4 - Fóris, Gábor; Sógor, László; Hendlein, Péter; Notaisz, Krisztián; Fidrich, Márta (Acta Cybernetica, 2002)
The aim of this paper is to present the design, specification, implementation and testing of a demonstration environment for examining a genuinely new communication technique. This technique ensures that 3G mobile networks can communicate with legacy Internet phones. More than one levels of the TCP/IP protocol family are necessary for the communication, so we had to develop device drivers and user level applications too. The different levels require various development techniques and tools, whose efficiently combined usage is emphasized.